1995
DOI: 10.1136/thx.50.10.1044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluticasone propionate and beclomethasone dipropionate on direct and indirect measurements of bronchial hyperresponsiveness in patients with stable asthma.

Abstract: Background -Fluticasone propionate is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 26 publications
0
36
1
Order By: Relevance
“…2, showing the advantage of ICS. However, when looking at comparative trials between FP in half the dose of BDP, being clinically equipotent [41,42], osteocalcin levels were significantly lowered after the double dose of BDP, with no change after FP [31,43]. Ayres et al [44] compared FP with BUD, but all patients already used 1-2 mg of ICS daily before the study.…”
Section: Biochemical Markers O F Bone Turnovermentioning
confidence: 99%
“…2, showing the advantage of ICS. However, when looking at comparative trials between FP in half the dose of BDP, being clinically equipotent [41,42], osteocalcin levels were significantly lowered after the double dose of BDP, with no change after FP [31,43]. Ayres et al [44] compared FP with BUD, but all patients already used 1-2 mg of ICS daily before the study.…”
Section: Biochemical Markers O F Bone Turnovermentioning
confidence: 99%
“…For instance, let us consider the difference in forced expiratory volume in one second (FEV1) following a randomized double-blind crossover trial of inhaled fluticasone propionate versus beclomethasone dipropionate in 21 asthmatic patients [54]. After the two 6 week treatment periods, the difference was 60 mL favouring fluticasone propionate.…”
Section: Study Intervention: Comparison Of Icsmentioning
confidence: 99%
“…The drugs were, however, sometimes administered by different inhaler devices or without a washout period, making the comparative efficacy of the two agents difficult to assess. [50][51][52][53][54][55]. A 2:1 equivalence of fluticasone over beclomethasone has been suggested, based on the observation of maintenance of the same degree of asthma control with a half-dose of fluticasone compared to beclomethasone [56,57].…”
Section: Study Intervention: Comparison Of Icsmentioning
confidence: 99%
“…It is also highly effective in decreasing airway hyper responsiveness [4,6]. It is widely used for the treatment of chronic asthma worldwide [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiologically, asthma is characterized by variable airway obstruction that is associated with an exaggerated response to various broncho-constrictor stimuli [1]. Airway inflammation is associated with airway hyper responsiveness, and several studies have shown that inhaled corticosteroids gradually reduce airway hyper responsiveness, possibly by their anti-inflammatory action [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%